Monetary policies and the achievement of bank profit objective - Alex Omankhanlen; Noah Ilori; Areghan Isibor; Lawrence Uchenna Okoye (Journal of Central Banking Theory and Practice, 2021)
This study examined the nexus between monetary policy and the achievement of a bank's profit objective. There have been lots of arguments about the benefits of monetary policy implementation on deposit money bank's operations, since the policies have been seen to impact on their performance. This study was carried out to establish the influence of variables like Liquidity Ratio, Interest and Money supply (M2), which are used as monetary policy instruments, on deposit money bank profitability objective. The study covers the period from 2002-2019. The Auto Regressive Distributed Lag and Error correction model were adopted in the analysis of the data. The study revealed that there was a positive long run relationship between Liquidity Ratio and deposit money bank's profitability; there also existed a negative long run relationship between interest rate and deposit money bank profitability; lastly, there existed a positive long run relationship between Money Supply (M2) and deposit money bank's profitability. Based on the findings, monetary authorities should put in place measures for Liquidity ratio, interest rates and M2 implementation to aid deposit money banks operations in the achievement of their profit objective.
Keywords: E52; E58; B22; 330; Monetary Policy; Profit; Banks; Interest Rates; Money; Credit